2018
DOI: 10.1520/acem20170027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pavement Condition Monitoring Frequency with Unequal Interval on Determining Pavement Service Life

Abstract: Accurate determination of pavement service life based on time-series pavement condition data is crucial to achieve many pavement maintenance and management objectives. Although pavement condition monitoring frequency is one of the most important influencing factors used to estimate pavement service life, previous studies and applications are mainly focused on different monitoring frequencies with equal time intervals. No studies investigating the effect of pavement monitoring frequency with unequal time interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Haider et al found that the frequency of condition data collection has a signi cant e ect on the performance prediction, higher variability in the data will introduce higher Squared Error (SE) in the tted model, and data collection frequency can be decreased with higher data accuracy [24]. Xu and Tsai studied the in uence of equal time interval and unequal time interval under the same monitoring frequency on prediction of pavement service life, they found the estimated accuracy of pavement service life would be signi cantly improved for unequal interval monitoring ways compared to that of equal interval monitoring ways under the same monitoring frequency [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Haider et al found that the frequency of condition data collection has a signi cant e ect on the performance prediction, higher variability in the data will introduce higher Squared Error (SE) in the tted model, and data collection frequency can be decreased with higher data accuracy [24]. Xu and Tsai studied the in uence of equal time interval and unequal time interval under the same monitoring frequency on prediction of pavement service life, they found the estimated accuracy of pavement service life would be signi cantly improved for unequal interval monitoring ways compared to that of equal interval monitoring ways under the same monitoring frequency [25,26].…”
Section: Introductionmentioning
confidence: 99%